THE PROBLEM OF THE IMAGE OF PUBLIC SERVANTS IN RUSSIA - T. A. Sergeeva; I. A. Savchenko (Вестник университета)
The formation of a favorable image is an integral part of the professional growth of public servants. Modern society imposes special demands on the image of public service employees. In this regard, their image should consist of a set of certain characteristics that emphasize the effectiveness and professionalism of their activities. To effectively create the image of public servants, it is necessary to pay attention to their personal characteristics, as well as to properly organize a PR company. A positive image is one of the main tools for the formation of communication between the state and society with the placement of significant priorities. The formation and development of a positive image is a multi-level, complex and responsible process, which requires hard work so that a public servant can inspire confidence and meet the expectations of citizens. Despite the fact that today the image is one of the most important tools of influence and management, its essence should be exclusively in the pursuit of good goals. It should be aimed at identifying and subsequently solving the main problems of citizens, as well as an active dialogue with society.